The Phenomenon of Library Anxiety in the Library of Universitas Pendidikan Indonesia - Algipari, Abizar; Azizah, Fauziyah; Fajrina, Farahdiba; Yasyfa, Taghsya Aghniya; Rabbah, Wanda Nadriah Fajrianti; Fuadin, Ahmad (Universitas Pendidikan Indonesia, 2023)
College libraries are the center of learning activities and information centers for the academic community. In its implementation, there are still often problems experienced by users that can trigger the phenomenon of Library Anxiety. This study aims to determine the phenomenon of Library Anxiety experienced by users when visiting and using facilities in the library, especially UPI Library and provide solutions to overcome the phenomenon of library anxiety. The research used two approaches, quantitative approach and qualitative approach. Data was obtained from questionnaires and literature studies on sources that have similar topics of discussion. The result of this research shows that there are still users in UPI Library who experience Library Anxiety phenomenon. Factors that influence the occurrence of Library Anxiety, including difficulties in finding a collection and using the available facilities, obstacles when using the electronic services provided, discrepancies between book data in the OPAC and book data on the shelves, and lack of knowledge of the correct book borrowing procedures. The solution that can be applied to reduce the phenomenon of Library Anxiety is to hold user education on the use of library facilities and services and a more responsive attitude of librarians.